Social hierarchy modulates drug reinforcement and protein phosphorylation in the nucleus accumbens - Xu, Liang; Zhou, Ruiyi; Zhong, Jiafeng; Huang, Yina; Zhu, Yingjie; Xu, Wei (Frontiers in Pharmacology, 2025)
IntroductionDrug reinforcement, a form of behavioral plasticity in which behavioral changes happen in response to a reinforcing drug, would finally lead to drug addiction after chronical drug exposure. Drug reinforcement is affected by genetic and environmental factors. Social hierarchy has been reported to regulate drug reinforcement and drug-seeking behaviors, but the underlying molecular mechanism is almost unknown.MethodsWe take advantage of the tube test to assess the social hierarchy between two co-housed rats. And then, we investigated the drug reinforcement between dominant and subordinate rats via conditioned place preference (CPP). Then we adopted 4-D label-free mass spectrometry to explore the complex phosphoproteome in the nucleus accumbens (NAc) between dominant and subordinate rats. Functional enrichment, protein-protein, motif analysis and kinase prediction interaction analysis were used to investigate the mechanism between substance use disorder and social hierarchy. Specifically, we identified histone deacetylase 4 (HDAC4) which has been previously shown to play critical roles in drug addiction as a key node protein by phosbind-SDS. Finally, we forcibly altered the social hierarchy of rats through behavioral training, follow by which we accessed the HDAC4 phosphorylation levels and drug reinforcement.ResultsIn this study, we found that methamphetamine exhibited stronger reinforcement in the subordinate rats. We identified 660 sites differing between dominant and subordinate rats via 4-D label-free mass spectrometry. Functional enrichment and protein-protein interaction analysis revealed that synaptic remodeling related pathways and substance use disorder related pathway are significantly characterized by social hierarchy. Motif analysis and kinase prediction showed that CaMKIIδ and its downstream proteins maybe the central hub. Phosbind-SDS revealed that higher HDAC4 phosphorylation levels in dominants. After the social hierarchy of rats were forcibly altered by behavioral training, the differences in HDAC4 phosphorylation levels induced by social hierarchy were eliminated, correspondingly the drug reinforcement is also reversed between the two group rats.DiscussionIn conclusion, our research proves that protein phosphorylation in the NAc may be a vital link between social hierarchy and drug reinforcement.